FAKTOR-FAKTOR YANG MEMPENGARUHI KESEHATAN MENTAL PERAWAT PENANGGULANGAN COVID-19 - Maramis, James Richard; Somba, Chintya Zhou Chen Mariam; Ruku, Denny Maurits (Fakultas Keperawatan, Universitas Klabat, 2025)
The daily rise in COVID-19 cases has intensified the workload for nurses treating patients with the virus, placing healthcare workers at heightened risk for mental health disorders. This study seeks to identify the factors that affect the mental health of nurses working in COVID-19 isolation units. A cross-sectional study was conducted involving 86 nurses, utilizing the Daily Spiritual Experience Scale (DSES), Social Provisions Scale (SPS), Coping Mechanisms Questionnaire (CMQ), and The Mental Health Inventory - 38 (MHI-38) instruments. The findings revealed that the average mental health score of participants was Good (74.03 ± 10.15). Mental Health exhibited a significant correlation with Spiritual Support (r = .40, p < .01), Social Support (r = .56, p < .01), and Coping Mechanisms (r = .25, p < .01). However, factors such as gender, education, and length of service showed no significant correlation. Hierarchical multiple regression test analysis identified two key predictors of mental health: Spiritual Support (β= .33, p< .01) and Social Support (β= .34, p< .01). These findings suggest that Spiritual Support, Social Support, and effective Coping Mechanisms can enhance an individual's mental health status, with both Spiritual and Social Support serving as predictors of mental health among nurses dealing with COVID-19. Healthcare institutions should proactively enhance social and spiritual support to mitigate the crisis's negative impact on nurses' mental health. Kasus COVID-19 yang terus bertambah setiap harinya, menyebabkan beban kerja perawat penanggulangan COVID-19 pun terus bertambah. Hal itulah yang menyebabkan tenaga kesehatan berisiko untuk mengalami gangguan kesehatan mental. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kesehatan mental perawat penanggulangan COVID-19. Cross sectional study design dilakukan pada 86 perawat yang bekerja di ruangan isolasi COVID-19 dengan instrumen Daily Spiritual Experience Scale (DSES), Social Provisions Scale (SPS), Coping Mechanisms Questionnaire (CMQ), dan The Mental Health Inventory - 38 (MHI–38). Hasil menunjukkan bahwa rerata kesehatan mental responden (74,03 ± 10,15). Kesehatan mental mempunyai hubungan yang signifikan dengan dukungan spiritual (r= 0,40, p< ,01), dukungan sosial (r= 0,56, p< 0,01), dan mekanisme koping (r= 0.25, p< 0,01); sedangkan jenis kelamin, pendidikan, dan lamanya bekerja tidak mempunyai hubungan yang signifikan. Uji hierarchical multiple regression memperlihatkan dua variabel merupakan predictor dari kesehatan mental seperti dukungan spiritual (β= 0,33, p< 0,01), dan dukungan sosial (β= 0,34, p< 0,01). Dukungan spiritual, dukungan sosial dan mekanisme koping yang baik dapat meningkatkan status kesehatan mental seseorang, sedangkan dukungan spiritual dan dukungan sosial merupakan prediktor dari kesehatan mental perawat penanganan COVID-19. Institusi kesehatan harus secara proaktif meningkatkan dukungan sosial dan spiritual untuk mengurangi dampak negatif krisis terhadap kesehatan mental perawat.